Activated Allogeneic NK Cells Preferentially Kill Poor Prognosis B-Cell Chronic Lymphocytic Leukemia Cells - Sánchez-Martínez, Diego; Lanuza, Pilar M.; Gómez, Natalia; Muntasell, Aura; Cisneros, Elisa; Moraru, Manuela; Azaceta, Gemma; Anel, Alberto; Martínez-Lostao, Luis; Villalba, Martin; Palomera, Luis; Vilches, Carlos; et al. (Frontiers in Immunology, 2016)
Mutational status of TP53 together with expression of wild-type (wt) IGHV represents the most widely accepted biomarkers, establishing a very poor prognosis in B-cell chronic lymphocytic leukemia (B-CLL) patients. Adoptive cell therapy using allogeneic HLA-mismatched Natural killer (NK) cells has emerged as an effective and safe alternative in the treatment of acute myeloid and lymphoid leukemias that do not respond to traditional therapies. We have described that allogeneic activated NK cells eliminate hematological cancer cell lines with multidrug resistance acquired by mutations in the apoptotic machinery. This effect depends on the activation protocol, being B-lymphoblastoid cell lines (LCLs) the most effective stimulus to activate NK cells. Here, we have further analyzed the molecular determinants involved in allogeneic NK cell recognition and elimination of B-CLL cells, including the expression of ligands of the main NK cell-activating receptors (NKG2D and NCRs) and HLA mismatch. We present preliminary data suggesting that B-CLL susceptibility significantly correlates with HLA mismatch between NK cell donor and B-CLL patient. Moreover, we show that the sensitivity of B-CLL cells to NK cells depends on the prognosis based on TP53 and IGHV mutational status. Cells from patients with worse prognosis (mutated TP53 and wt IGHV) are the most susceptible to activated NK cells. Hence, B-CLL prognosis may predict the efficacy of allogenic activated NK cells, and, thus, NK cell transfer represents a good alternative to treat poor prognosis B-CLL patients who present a very short life expectancy due to lack of effective treatments.